Pengaruh PAD dan DAU terhadap Pertumbuhan Ekonomi melalui Belanja Modal di Provinsi Bali - Sumartini, Ni Komang Ayuk; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
ABSTRACT The difference in resources and potential possessed by each district / city in the province of Bali provides enormous influence the creation pattern of development and economic growth is not uniform. This lack of uniformity results in a difference in the growth and development of an area. This study aimed to determine the effect of PAD and DAU to economic growth through an intermediary capital expenditures in the district / city of Bali province. Source of data used is secondary data using panel data (time series data and cross section 7 years 8 counties and one city). The analysis technique used is the path analysis with SPSS. The results of the analysis indicate that the PAD and DAU has no effect on capital expenditures, local revenues had no effect on economic growth, DAU and capital expenditures and significant positive effect on economic growth, revenue and DAU effect on economic growth through capital expenditure on district / city in the province of Bali.
Keywords: local revenues, general allocation fund, economic growth and capital expenditure